2020
DOI: 10.1136/lupus-2020-000429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on disease flares in patients with systemic lupus erythematosus: post hoc analyses from two randomised trials

Abstract: ObjectiveTo confirm that metformin prevents flares in patients with SLE with low disease activity, we performed a post hoc analysis combining our previous two randomised trials.MethodsPost hoc analyses were performed on data from the open-labelled proof-of-concept trial (n=113, ChiCTR-TRC-12002419) and placebo-controlled ‘Met Lupus’ trial (n=140, NCT02741960) comparing the efficacy of metformin versus placebo/nil add-on to standard therapy in patients with SLE with low disease activity (SELENA-SLEDAI ≤4). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 15 publications
(17 reference statements)
1
23
0
Order By: Relevance
“…This means that while the data may seem contradictory it is more likely that there is a complex feedback network regulating IFN signaling and mitochondrial oxidative stress in SLE. Along with the clinical progress of repurposing metabolic modulators, such as metformin, in the management of SLE [8, 32,33], our data may offer additional insight into the immunometabolism of SLE. Furthermore, attempts to predict the target genes of tRF-3009 (3'UTR region and promoter region) using miRNA prediction databases were a failure due to the lack of intersection between predicted target genes and transcriptome data (Supplementary Tables 4, 6, 7).…”
Section: Discussionmentioning
confidence: 93%
“…This means that while the data may seem contradictory it is more likely that there is a complex feedback network regulating IFN signaling and mitochondrial oxidative stress in SLE. Along with the clinical progress of repurposing metabolic modulators, such as metformin, in the management of SLE [8, 32,33], our data may offer additional insight into the immunometabolism of SLE. Furthermore, attempts to predict the target genes of tRF-3009 (3'UTR region and promoter region) using miRNA prediction databases were a failure due to the lack of intersection between predicted target genes and transcriptome data (Supplementary Tables 4, 6, 7).…”
Section: Discussionmentioning
confidence: 93%
“…In a separate study, metformin given alongside the glycolytic inhibitor 2-DG was shown to ameliorate autoimmune pathology in lupus-prone mice (134). A recent clinical trial into the efficacy of metformin in SLE patients found no efficacy in reducing the incidence of disease flares, although pooled analysis with a previous trial suggested a modest reduction in flare incidence was achieved, warranting further investigation (135,136).…”
Section: B Cell Metabolism and Autophagy As Therapeutic Targetsmentioning
confidence: 97%
“…Metformin synergizes with 2-DG in the treatment of lupus mice (33) and has shown protective effects in some models of arthritis and Sjöegren syndrome (37)(38)(39), but these studies are focussed on acquired immunity. In humans, clinical trials have shown that metformin ameliorates SLE activity, at least in part by reducing neutrophil activation and plasmacytoid dendritic cell function (40,41).…”
Section: Manipulation Of Metabolic Pathwaysmentioning
confidence: 99%